LANGUAGE ACQUISITION AND LEARNING ON CHILDREN - Fernandes Arung (Journal of English Education, 2016)
Debating on Second Language Acquisition is not merely in terms of concept but also the real phenomena which postulate each research result. It needs more investigation on SLA due to the various realities on how children and adults acquire and learn any language. This research aims to describe how children and adults acquire and learn their first and second language. Participants consisted of children and adults whose ages determined by the researcher based on the purposive sampling technique. They were all six persons and chosen based on certain characteristics. Content analysis technique was applied in order to analyze all data gained. The result showed that since human alive inside mother’s womb especially at up to the age of three months, a fetus has tried to acquire sounds subconsciously. Language proficiency is really determined by three factors of Phased Process Approach namely Subconscious Acquisition, Conscious Acquisition, and Learning. The ideal time for learning something is begun from the age of 2 or 3 years old, by the fact that children have had the ability to bear a meaning on any input that they catch. The learning process has been begun within the process of acquisition. Based on the findings, it is clear that the children acquire the language step by step based on the development of the brain. Children acquire language is just the same as adult in acquiring the language although there will be some constraints faced by adult concern with the first language because adult has had the strong basis of the first language just than children.